The The Influence of The Role Playing Method in PKn Subjects on Students' Learning Interest in Class III SD Muhammadiyah 19. - Vanessa, Dea (Journal of Elementary School Education, 2023)
This research was motivated by the lack of student interest in learning Civics in class III at SD Muhammadiyah 19, because the methods used by the teacher were less interesting. The formulation of the problem in this research is, How is the influence of students' interest in learning before using the Role Playing method in Civics learning. How is the influence of students' interest in learning after using the Role Playing method in Civics subjects. How is the influence of students' interest in learning in Civics learning using the Role method? Playing. The type of research used is experimentation. The subjects of this research were 26 class III students. Data collection techniques use research instruments in the form of observation sheets.Student learning in class III obtained an average Pretest score of 47.50 and after being given treatment and being given a Post-test it increased to 88.50. This shows that the use of the Role Playing method has an influence on student learning outcomes in class III.Thus, the Role Playing method can be used as a learning method that can increase students' interest in learning.